GAMBARAN PENGETAHUAN MASYARAKAT TERHADAP KESIAPAN BENCANA (DISASTER PREPAREDNESS) - Siti Yulipah Agustini; Ayu Prawesti; Sandra Pebrianti (Jurnal Ilmu Keperawatan Indonesia, 2020)
Garut Regency is one of the regencies in West Java that is prone to disasters, floods, landslides, earthquakes, fires and tornado winds. Readiness is part of the initial step for disaster. Readiness is an activity carried out to anticipate disasters through organizing activity with appropriate steps. The purpose of this research was find out the description of community knowledge on disaster readiness in Garut Regency. This research method used descriptive quantitative. The instrument in collecting data used questionnaires, with cluster random sampling technique by processing data using slovin formula as many as 84 people based on frequency distribution. The results showed that the knowledge of community in five districts of Garut Regency with the highest category was bad category 47 (56.0%). The majority of disaster readiness knowledge in Garut Regency showed that most public knowledge was bad, it needs to be given information and counseling related to the concept of disasters and how to prevent them. Disaster readiness is very important in disaster safety. The results of this study were expected to be used as a basic material and experience for the provision and knowledge of disaster readiness, with the aim of saving the lives, property and reducing casualties.Keywords  : Disaster Readiness, Knowledge